THE EFFECT OF PLANTING DEPTH ON THE GROWTH OF Kappaphycus alvarezii FROM TISSUE CULTURE IN SERIWE VILLAGE WATERS, EAST LOMBOK - Baiq Hilda Astriana; Dewi Putri Lestari; Muhammad Junaidi; Muhammad Marzuki (Universitas Mataram, 2019)
This research aimed to address the effect of seaweed Kappaphycus alvarezii (result of tissue culture) planting depth on the seaweed growth. This reasearch was conducted in Seriwe Village water, Jerowaru subdistrict, East Lombok Regency known as the largest minapolitan area in West Nusa Tenggara Province. Method used in this research was completely randomized design consisting of five treatments of planting depth which were 0.15 m, 0.5 m, 1 m, 1.5 m, and 2 m. Each treatment was repeated four times. Main parameters measured were the seaweed Daily Growth Rate, Absolute Growth. In addition, water quality parameters measured were temperature, light intensity, dissolved oxygen, salinity, pH, Phosphate, ammoniac, TAN, TDS, and current speed. Data collected were analyzed using ANOVA with significant level of 5% and any significant difference between the treatments was analyzed using LSD in the same significant level. The result of data analysis shows that the most optimum planting depth appropriate for K. alvarezii growth is 0.5 m.